Pengaruh Mobilisasi Progresif Level II terhadap Tekanan Darah dan Saturasi Oksigen pada Pasien Kritis di Ruang ICU - Khairiyah, Atikah; Mardiyono, Mardiyono; Negoro, M. Syamsul Arif Setiyo (JURNAL KEPERAWATAN MERSI, 2025)
Background: Critical patients are admitted to the ICU, undergoing bed rest and immobilization. Not only do they develop pressure ulcers, but also their hemodynamics and saturation may decline gradually. Passive ROM is usually administered to prevent joint shifts and to maintain blood pressure and saturation. Progressive mobilization is initiated to maintain blood pressure and saturation. Objective: To evaluate progressive mobilisation to maintain blood pressure, systolic and diastolic pressure, and increase saturation. Method: Penelitian adalah pre-post test control group design. Samples were recruited by consecutive sampling for 18 subjects. The intervention group was administered progressive mobilization level II for 30 minutes for 3 days, and the control group was administered passive ROM for 3 days. Data were analysed by paired t-test and independent t-test. Results: Passive progressive mobilization level II effectively decreases systolic blood pressure (p=0.022) and diastolic blood pressure (p=0.000), and significantly increases saturation (p=0.000). Conclusion: Passive progressive mobilization level II is more effective in decreasing blood pressure and increasing saturation than passive ROM.